Madeira island – destination image and tourists loyalty - Machado, Luiz Pinto (2021)
This study uses a Logit model to examine the probability of the image of the tourism destination Madeira, a Portuguese autonomous insular region, being strengthened after the tourists’s visit to the destination. The results of the empirical study are based on a survey carried out to tourists during their visit to the island of Madeira, between March and July 2008. The model confirms that the probability of enhancing Madeira’s tourism destination image after the visit is explained by several independent variables, gathered from the literature review. The findings of the study intend to call local authorities’s attention to the importance of repeated tourists due to the impact that their enhanced image of Madeira may have on the economic sustainability of the destination and on the potential savings in promotion investment. This happens because the client's loyalty brings a high return of the destination’s marketing investment. The conclusions can also help the decision makers of the tourism sector of the island of Madeira to better plan their destination marketing activities.